2012
DOI: 10.5152/balkanmedj.2011.014
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Quercetin Against Renal Toxicity Induced by Cadmium in Rats

Abstract: Objective: The aim of the present study was to examine the protective effect of quercetine (QE) against cadmium (Cd)-induced renal toxicity. Material and Methods:A total of 24 male Wistar albino rats were divided into three groups: control, Cd-treated and Cd-treated with QE; each group containing 8 animals. The Cd-treated group was injected subcutaneously with CdCl2 dissolved in saline in the dose of 2 ml/kg/day for 30 days, resulting in a dosage of 1 mg/kg Cd. The rats in the QE treated groups were given QE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(40 reference statements)
4
12
0
Order By: Relevance
“…2e). A similar result was obtained by [13,51]. On the other hand, glomular parts exhibited minimal histologic changes (Fig.…”
Section: Kidney Histopathologysupporting
confidence: 74%
“…2e). A similar result was obtained by [13,51]. On the other hand, glomular parts exhibited minimal histologic changes (Fig.…”
Section: Kidney Histopathologysupporting
confidence: 74%
“…Thus, since apoptosis may be one of the main features of Cd intoxication, it seems necessary to conduct more effective studies on the phenomenon in the tubular epithelium after exposure to higher doses of Cd. Exposure to Cd has been shown to induce apoptosis of the proximal tubular cells and, therefore, disrupt kidney function [18,39,41,42]. Yuan et al [43] confirmed that Cd disrupted apoptosis in the kidneys.…”
Section: Discussionmentioning
confidence: 91%
“…The administration of Cd resulted in various damages to the proximal tubules and glomeruli of the kidneys. Quercetin, an anti-oxidant substance, was shown to reverse this damage [18]. In 2011, Fouad and Jresat administered mice with 1.2 mg Cd for 9 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important Cd sources affecting human life are cigarette smoke, refined nutrients, water pipes, coffee, tea, products released by burning coal, shellfishes, fertilizers used, dyes and batteries containing Cd, and flue gases released in industrial production stages [7]. Occupational and environmental Cd exposure cause serious damages in the tissues like the placenta, kidney, liver, testis, heart, brain, and lungs [8][9][10][11][12][13][14][15]. Several investigations confirmed its transport across the placenta and accumulation in fetuses [16,17].…”
Section: Introductionmentioning
confidence: 99%